TRAF3/CYLD mutations identify a distinct subset of human papillomavirus‐associated head and neck squamous cell carcinoma. Issue 10 (13th March 2017) - Hajek, Michael; Sewell, Andrew; Kaech, Susan; Burtness, Barbara; Yarbrough, Wendell G.; Issaeva, Natalia
Abstract : BACKGROUND: The incidence of human papillomavirus (HPV)‐associated (HPV‐positive) head and neck squamous cell carcinoma (HNSCC) of the oropharynx has dramatically increased over the last decade and continues to rise. Newly diagnosed HPV‐positive HNSCCs in the United States currently outnumber any other HPV‐associated cancers, including cervical cancer. Despite introduction of the HPV vaccine, the epidemic of HPV‐positive HNSCC is expected to continue for approximately 60 years. Compared with patients who have tobacco‐associated HNSCC, those who have HPV‐positive HNSCC have better overall survival and response to treatment. Current treatment, including chemotherapy and radiation therapy, is associated with lifelong morbidity, and there are limited treatments and no curative options for patients who develop recurrent metastatic disease. Therapeutic de‐escalation (decreased radiation dose) is being tested through clinical trials; however, those studies select patients based solely on tumor and patient smoking characteristics. Mechanisms of HPV‐driven carcinogenesis in HNSCC are not well understood, which limits new therapeutic strategies and hinders the appropriate selection of patients for de‐escalation therapy. METHODS: The authors analyzed HNSCC data from The Cancer Genome Atlas to identify molecular characteristics that correlate with outcomes and integration status of the HPV genome. RESULTS: The current investigations identified a subset of HPV‐positive HNSCCs with mutations in the genes TRAF3 (tumor necrosis factor receptor‐associated factor 3) and CYLD (cylindromatosis lysine 63 deubiquitinase). Defects in TRAF3 and CYLD correlated with the activation of transcriptional factor nuclear factor κB, episomal HPV status of tumors, and improved patient survival. CONCLUSIONS: Defects in TRAF3 / CYLD were accompanied with the activation of nuclear factor κB signaling and maintenance of episomal HPV in tumors, suggesting that these mutations may support an alternative mechanism of HPV tumorigenesis in head and neck tumors. Cancer 2017;123:1778–1790 . © 2017 The Authors . Cancer published by Wiley Periodicals, Inc. on behalf of American Cancer Society . This is an open access article under the terms of the Creative Commons Attribution NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes. Abstract : Human papillomavirus‐associated head and neck cancer tends to respond better to treatment compared with tobacco‐associated tumors; however, patients suffer severe and long‐lasting side effects. Somatic mutations in the genes TRAF3 and CYLD identified in The Cancer Genome Atlas data set are correlated with the activation of nuclear factor‐κB, define a distinct etiologic subset of head and neck cancers, and will be useful as biomarkers for predicting improved prognosis and selecting patients with human papillomavirus‐positive head and neck cancer who may be successfully treated with de‐escalating therapy. See also pages 1695‐98.